2021
DOI: 10.24875/ric.20000470
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Pathogenicity of CDH1 Gene Variants in Patients with Early-onset Diffuse Gastric Cancer from Western Mexico

Abstract: Background: Early-onset diffuse gastric cancer (EODGC) occurs at or before 50 years of age. Pathogenic mutations and germline deletions in the CDH1 gene (E-cadherin) are well-documented genetic factors associated with the causes of EODGC. Objective: The objective of the study was to study CDH1 germline variants and their potential functional impact in patients with EODGC in a Mexican population. Methods: We studied seven EODGC patients from a biomedical research center in western Mexico. Variants were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The rs16260 variant was previously associated to risk of DGC in our population, with an OR of 1.98 (95% CI 1.01-3.98) for heterozygotes and 6.5 (95% CI 2.1-19.6) for homozygotes 57 , and the others are reported as having uncertain significance (c.531 + 4G > A and c.2331C > G) or have not been reported (c. −273G > A, c.388-83G > A,C, and c.388-48A > G), all of which were included in the predictive analysis. We reported in a previous study that allele A of variant c. −273G > A could modify the binding sites of the transcription factors IRF3 and SP2 58 . Prediction for the intronic variants c.388-83G > A,C and c.388-48A > G with the NNSplice and NetGene2 programs showed that splicing would not be affected.…”
Section: Discussionmentioning
confidence: 89%
“…The rs16260 variant was previously associated to risk of DGC in our population, with an OR of 1.98 (95% CI 1.01-3.98) for heterozygotes and 6.5 (95% CI 2.1-19.6) for homozygotes 57 , and the others are reported as having uncertain significance (c.531 + 4G > A and c.2331C > G) or have not been reported (c. −273G > A, c.388-83G > A,C, and c.388-48A > G), all of which were included in the predictive analysis. We reported in a previous study that allele A of variant c. −273G > A could modify the binding sites of the transcription factors IRF3 and SP2 58 . Prediction for the intronic variants c.388-83G > A,C and c.388-48A > G with the NNSplice and NetGene2 programs showed that splicing would not be affected.…”
Section: Discussionmentioning
confidence: 89%
“…[23] Therefore, loss of E-cadherin function during tumor progression could be partially attributable to SNPs of putative susceptibility alleles. [24] Numerous studies have proved the associations between CDH1 polymorphisms and the risk of GC in humans. [25][26][27] The most widely studied sites are CDH1 rs16260 (−160C > A) and rs5030625 (−347G > GA) in the promoter region, which can decrease the transcription efficiency of the gene.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Therefore, loss of E-cadherin function during tumor progression could be partially attributable to SNPs of putative susceptibility alleles. [ 24 ]…”
Section: Introductionmentioning
confidence: 99%